(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper explores the correlation between Antisocial Personality Disorder (ASPD) and serial killing, assessing the extent of their association. It examines ASPD’s diagnostic criteria, root causes, and the role of neurological deficiencies and genetic factors in aggression. By analysing past research and considering environmental, societal, and psychological influences, the paper seeks to provide a well-rounded answer to the research question: To what extent is ASPD responsible for serial killing?